Mekka in the Latter Part of the 19th Century - Isa Blumi (International Institute of Islamic Thought, 2008)
The annual spectacle of millions of pilgrims flooding Makkah has captured the imagination of generations of readers. This interest in the hajj, however, has not necessarily produced quality scholarship. From crude ethnographic summaries to careful narratives of spiritual attainment, the literature has been inconsistent at best. Brill’s republishing of Dutch scholar Christiaan Snouck Hurgronje’s (1857-1936) forgotten work offers the modern reader not only an invaluable window into the hajj as practiced before the age of mass communication, but provides a hitherto neglected discussion on the social, cultural, political, and economic impact that the experience had upon Muslims. Often lost in the generalizations one finds in descriptions of the annual pilgrimage, the world in which the reader is thrust while reading this book offers a Makkah that is far more culturally dynamic than expected. Hurgronje’s world is one filled with cultural and doctrinal variances that aremanifested in the different ways in which Muslims worshiped, clothed themselves, and ultimately socialized while in Makkah. In this sense, his careful study of life over the months leading to the hajj exposes the reader to a fluid cultural and economic process that constantly transforms, leaving the reader with the impression that life was not, as the clichés so often try to instill, “timeless.” Hurgronje, to his credit, is not interested in retelling the Orientalist trope; rather, he strives to provide a serious ethnographic and historical study. As Hurgronje himself writes, this is a study to help non-Muslims, especially fellow Dutchmen, understand their Muslim subjects living in the Far East. For this reason, the book’s final part focuses exclusively on the Makkan experience of Dutch subjects. In this regard, it is a careful analysis of how Muslims from Java, Borneo, and Sumatra interacted with fellow Muslims; socialized in this cosmopolitan milieu; and adopted numerous personal and collective activities during their stay. That being said, it is especially impressive that this study is not meant to be only a tool for colonial governance ...